KAJIAN ARSITEKTUR KONTEKSTUAL PADA SUMBU, SIMETRI, DAN HIRARKI BANGUNAN AULA BARAT ITB - Titieandy Lie (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2021)
The designing of new buildings at Bandung Institute of Technology (ITB) campus has created building structures which are varied and tend to be non-contextual, not aligned with the older buildings or the conservation of the building as the existing ones. Therefore, this study is conducted by following some systematic steps, namely: (1) investigating the concept of the ITB campus initial design; (2) describing the architectural values of the West Hall building; (3) making studies on the axis, symmetry, and hierarchy of the West Hall Building.The objective of this study is to determine the basis for designing contextual architecture through axis, symmetry, and hierarchy in the West Hall building, which is a reference to the planning and design of new buildings around it.